Mechanism of nuclear movements in a multinucleated cell - Gibeaux, Romain; Nédélec, François (Molecular biology of the cell, 2017)
A simple 3D stochastic model captures key features of nuclei movements observed in the hyphae of Ashbya gossypii. These motions are driven by dynein motors pulling on microtubules, similar to the oscillations of the anaphase spindle in budding yeast, but the regulation of the two systems diverged, possibly as a result of evolutionary tinkering., Multinucleated cells are important in many organisms, but the mechanisms governing the movements of nuclei sharing a common cytoplasm are not understood. In the hyphae of the plant pathogenic fungus Ashbya gossypii, nuclei move back and forth, occasionally bypassing each other, preventing the formation of nuclear clusters. This is essential for genetic stability. These movements depend on cytoplasmic microtubules emanating from the nuclei that are pulled by dynein motors anchored at the cortex. Using three-dimensional stochastic simulations with parameters constrained by the literature, we predict the cortical anchor density from the characteristics of nuclear movements. The model accounts for the complex nuclear movements seen in vivo, using a minimal set of experimentally determined ingredients. Of interest, these ingredients power the oscillations of the anaphase spindle in budding yeast, but in A. gossypii, this system is not restricted to a specific nuclear cycle stage, possibly as a result of adaptation to hyphal growth and multinuclearity.